Comparative Secretome and Functional Analyses Reveal Glycoside Hydrolase Family 30 and Cysteine Peptidase as Virulence Determinants in the Pinewood Nematode Bursaphelenchus xylophilus - Shinya, Ryoji; Kirino, Haru; Morisaka, Hironobu; Takeuchi-Kaneko, Yuko; Futai, Kazuyoshi; Ueda, Mitsuyoshi (Frontiers in Plant Science, 2021)
Pine wilt disease, caused by the pinewood nematode, Bursaphelenchus xylophilus, is one of the world’s most serious tree diseases. Although the B. xylophilus whole-genome sequence and comprehensive secretome profile have been determined over the past decade, it remains unclear what molecules are critical in pine wilt disease and govern B. xylophilus virulence in host pine trees. Here, a comparative secretome analysis among four isolates of B. xylophilus with distinct virulence levels was performed to identify virulence determinants. The four candidate virulence determinants of B. xylophilus highly secreted in virulent isolates included lipase (Bx-lip1), glycoside hydrolase family 30 (Bx-GH30), and two C1A family cysteine peptidases (Bx-CAT1 and Bx-CAT2). To validate the quantitative differences in the four potential virulence determinants among virulence groups at the protein level, we used real-time reverse-transcription polymerase chain reaction analysis to investigate these determinants at the transcript level at three time points: pre-inoculation, 3 days after inoculation (dai), and 7 dai into pine seedlings. The transcript levels of Bx-CAT1, Bx-CAT2, and Bx-GH30 were significantly higher in virulent isolates than in avirulent isolates at pre-inoculation and 3 dai. A subsequent leaf-disc assay based on transient overexpression in Nicotiana benthamiana revealed that the GH30 candidate virulent factor caused cell death in the plant. Furthermore, we demonstrated that Bx-CAT2 was involved in nutrient uptake for fungal feeding via soaking-mediated RNA interference. These findings indicate that the secreted proteins Bx-GH30 and Bx-CAT2 contribute to B. xylophilus virulence in host pine trees and may be involved in pine wilt disease.